2014
DOI: 10.3390/ijms151017366
|View full text |Cite
|
Sign up to set email alerts
|

Intermittently Administered Parathyroid Hormone [1–34] Promotes Tendon-Bone Healing in a Rat Model

Abstract: The objective of this study was to investigate whether intermittent administration of parathyroid hormone [1–34] (PTH[1–34]) promotes tendon-bone healing after anterior cruciate ligament (ACL) reconstruction in vivo. A rat model of ACL reconstruction with autograft was established at the left hind leg. Every day, injections of 60 μg PTH[1–34]/kg subcutaneously were given to the PTH group rats (n = 10) for four weeks, and the controls (n = 10) received saline. The tendon-bone healing process was evaluated by mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 52 publications
0
25
0
Order By: Relevance
“…PTH plays an important role in the treatment of osteoporosis due to its anabolic effect, and PTH therapy is known to enhance bone formation and improve fracture healing . Many studies have shown that PTH increases chondrocyte recruitment and differentiation, and intermittently administered PTH has been shown to improve trabecular bone thickness and microarchitecture . PTH use can directly stimulate osteocytes and chondrocytes and promote growth factor expression .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PTH plays an important role in the treatment of osteoporosis due to its anabolic effect, and PTH therapy is known to enhance bone formation and improve fracture healing . Many studies have shown that PTH increases chondrocyte recruitment and differentiation, and intermittently administered PTH has been shown to improve trabecular bone thickness and microarchitecture . PTH use can directly stimulate osteocytes and chondrocytes and promote growth factor expression .…”
Section: Discussionmentioning
confidence: 99%
“…The tendon‐to‐bone repair mechanism is similar to bone healing, which is dependent on the proliferation and differentiation of mesenchymal stem cells, matrix formation, and tissue remodeling . During the tendon–bone healing process, PTH can bind to PTH1R in mesenchymal stem cells and osteoblasts accelerate tendon–bone healing . Chen et al demonstrated that PTH could increase the proliferation of mesenchymal stem cells and affect tendon–bone healing process by regulating the secretion of certain factors from mesenchymal stem cells, osteocytes, or osteoblasts.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, PTH treatment reduced the expression of the chondrocytic genes aggrecan and sox9, suggesting that it may also help in the maintenance of a tenocytic lineage. The clinical correlation between high serum PTH and poor tendon health is likely due to continuous exposure to PTH and increased bone resorbing osteoclast activity at the tendon-bone interface 14,15 , rather than the short or intermittent administration discussed in this paper and the pre-clinical studies published to date [7][8][9] . These results suggest that PTH may have a slight beneficial effect on tendon healing, particularly in the tendon-bone area as pre-clinical studies have suggested.…”
Section: Discussionmentioning
confidence: 99%
“…However, when taken into context with previously published data, it may have a use in treating tendonbone defects, where tendon, fibrocartilage and bone occur within millimetres. Clinically, hypothyroidism has been linked to musculoskeletal problems in humans 12 , and increased serum PTH is associated with tendon laxity and spontaneous tendon rupture [13][14][15] , although pre-clinical in vivo studies using PTH suggest it may have some benefit in tendon healing [7][8][9] . In our study PTH had no effect on tendon proliferation or collagen production, but did increase the expression of decorin, which plays a role in matrix assembly and could have direct implications on collagen fibrillogenesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation